Filipin recognizes both GM1 and cholesterol in GM1 gangliosidosis mouse brain - Julian R. Arthur (Journal of Lipid Research, 2011)
Filipin is an antibiotic polyene widely used as a histochemical marker for cholesterol. We previously reported cholesterol/filipin-positive staining in brain of β-galactosidase (β-gal) knockout (−/−) mice (GM1 gangliosidosis). The content and distribution of cholesterol and gangliosides was analyzed in plasma membrane (PM) and microsomal (MS) fractions from whole-brain tissue of 15 week-old control (β-gal+/−) and GM1 gangliosidosis (β-gal−/−) mice. Total ganglioside content (μg sialic acid/mg protein) was 3-fold and 7-fold greater in the PM and MS fractions, respectively, in βgal−/− mice than in βgal+/− mice. GM1 content was 30-fold and 50-fold greater in the PM and MS fractions, respectively. In contrast, unesterified cholesterol content (μg/mg protein) was similar in the PM and the MS fractions of the βgal−/− and βgal+/− mice. Filipin is known to bind to various sterol derivatives and phospholipids on thin-layer chromatograms. Biochemical evidence is presented showing that filipin also binds to GM1 with an affinity similar to that for cholesterol, with a corresponding fluorescent reaction. Our data suggest that the GM1 storage seen in the β-gal−/− mouse contributes to the filipin ultraviolet fluorescence observed in GM1 gangliosidosis brain. The data indicate that in addition to cholesterol, filipin can also be useful for detecting GM1.